Study on the Pyrolysis Behaviors of Urea-Formaldehyde Resin and Rice Straw Mixed Pellets - Li, Xiaoteng; Bing, Huilin; Luo, Siyi; Zhang, Weiwei; Zuo, Zongliang; Ren, Dongdong (Frontiers in Energy Research, 2022)
In order to study the effect of biomass on the pyrolysis characteristics of urea-formaldehyde resin, the thermogravimetric experiment is carried out by blending urea-formaldehyde resin with rice straw in different proportions, and kinetics analysis was done to get the mechanism of pyrolysis. The results show that the pyrolysis process of urea-formaldehyde resin powder and the mixtures of urea-formaldehyde resin and rice straw can be divided into three stages, and the second stage is the rapid decomposition stage of volatile matter, which is the main stage. The reaction orders of urea-formaldehyde resin and the mixtures of urea-formaldehyde resin and rice straw were determined by Coats-Redfern method to be 1, and the result of pyrolysis kinetics calculation shows that the activation energy of the pyrolysis reaction reduces with the addition of rice straw, which is beneficial to the pyrolysis process. In the process of pellet preparation, the falling strength and compressive strength of urea-formaldehyde resin pellets can be improved by adding appropriate proportion of rice straw. Moreover, the mass fraction of pyrolytic carbon is the highest (23.93 %), when the ratio of urea formaldehyde resin to rice straw is 3:2. When the ratio of urea-formaldehyde resin to rice straw is 4:1, the mass fraction of pyrolysis oil was the highest, which is 43.21 %.